Influencing Factors of Psychosocial Stress among Korean Adults during the COVID-19 Outbreak - Jina Kim (International Journal of Environmental Research and Public Health, 2021)
The restriction of an individual’s daily life due to the strengthening of quarantine and lockdown increases psychosocial stress. This study aimed to determine the factors that influence psychosocial stress during a period of strict quarantine and lockdown to curb the COVID-19 pandemic in Korea. A total of 338 adults participated in a cross-sectional online survey conducted from 19–25 May 2020, which measured knowledge of COVID-19, health belief, resilience, and psychosocial stress. According to the results, there was no difference between the participants’ scores from the Daegu area (with concentrated confirmed COVID-19 cases) and the non-Daegu area except for health belief. Eighty-two percent of participants constituted the high-risk group for psychosocial stress. Individual resilience was positively correlated with health belief and negatively correlated with psychosocial stress (p < 0.001). Further, the following factors affected the level of psychosocial stress: resilience, subjective health status, and monthly household income, with an explanatory power of 39.8%. Therefore, those with higher subjective health and higher monthly household income experienced higher psychosocial stress, whereas higher resilience indicated lower psychosocial stress.